2020
DOI: 10.1016/j.dsx.2020.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Use of pioglitazone in people with type 2 diabetes mellitus with coronavirus disease 2019 (COVID-19): Boon or bane?

Abstract: Background and aims People with type 2 diabetes mellitus (T2DM) have increased morbidity and mortality due to coronavirus disease-19(COVID-19). It has been speculated that use of pioglitazone might increase such risk. The aim of our brief commentary is to review the safety of pioglitazone in people with T2DM and mild/moderate COVID-19. Methods We searched PubMed database using specific keywords related to our aims till May 15, 2020. Full text of relevant articles publis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…For this reason, SARS-CoV-2 pathophysiology is related to its interaction with adipocytes and adipose-like cells that favor the differentiation of lung lipofibroblasts into myofibroblasts ( 79 ). Pioglitazone also increases ACE2 expression in insulin-sensitive tissues, normalizing blood glucose and attenuating acute kidney injury through the amelioration of the expression of renal ADAM17 ( 80 ). Therefore, thiazolidinediones can reduce the interaction between SARS-CoV-2 and adipocytes with subsequent reduction of COVID-19 severity ( Figure 6 ).…”
Section: Diabetic Pharmacotherapy and Covid-19mentioning
confidence: 99%
“…For this reason, SARS-CoV-2 pathophysiology is related to its interaction with adipocytes and adipose-like cells that favor the differentiation of lung lipofibroblasts into myofibroblasts ( 79 ). Pioglitazone also increases ACE2 expression in insulin-sensitive tissues, normalizing blood glucose and attenuating acute kidney injury through the amelioration of the expression of renal ADAM17 ( 80 ). Therefore, thiazolidinediones can reduce the interaction between SARS-CoV-2 and adipocytes with subsequent reduction of COVID-19 severity ( Figure 6 ).…”
Section: Diabetic Pharmacotherapy and Covid-19mentioning
confidence: 99%
“…Several reports have indicated that PPARg agonists could be candidates for modulating the cytokine storm in the COVID-19 disease (87,149,150). A possible therapeutic role for pioglitazone has been identified with respect to the SARS-CoV-2 infection (16).…”
Section: Pparg Agonists In Sars-cov-2 Infectionmentioning
confidence: 99%
“…Several studies have shown that, in numerous diseases (11)(12)(13)(14), the WNT/b-catenin pathway interacts with PPARg (peroxisome proliferator-activated receptor gamma) in an opposing interplay, with the effects of one opposing those of the other. Recent studies have also highlighted the possible role of PPARg agonists as modulators of inflammatory and immunomodulatory drugs by targeting the cytokine storm in COVID-19 patients (15,16). This review focuses on the opposing interplay between WNT/b-catenin and PPARg in SARS-CoV-2 infection and the potential role of PPARg agonists in this context.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, due to its adverse effects such as fluid retention (Alam et al, 2019), pioglitazone was recommended for discontinuation in acutely ill patients. In contrast, Mukherjee et al considered that pioglitazone had more potential benefit than harm, and it could be continued in people with moderate COVID-19 (Jagat et al, 2020). Indeed, pioglitazone has been shown to decrease the secretion of various proinflammatory cytokines in the monocytes and macrophages (Bassaganya-Riera et al, 2010).…”
Section: Pioglitazonementioning
confidence: 99%